Science for art: multi-years' evaluations of biocidal efficacy in support of artwork conservation - Bartoli, Flavia; Isola, Daniela; Casanova Municchia, Annalaura; Kumbaric, Alma; Caneva, Giulia (Frontiers in Microbiology, 2023)
In recent decades, the relationship between Science and Art has been gradually strengthened through the use of diagnostic, conservation, and valorization technologies. New technologies can also be used to support the creation and durability of bio-artworks. Within such a context, starting from the Spring of 2014, we performed in situ experimentations to eventually increase the durability of the graphical artwork of William Kentridge on the Lungotevere embankments, whose creation was scheduled in the following years. We applied various combinations and concentrations of three different biocides (Algophase, Biotin R, and Preventol R80) and two water repellents (Hydrophase surfaces and Silo 111) on 34 test areas. However, the artist preferred to leave his artwork to a natural fading. Right before the realization of the graphical artwork “Triumph and Laments of Rome” in 2016, just the black biological colonizations mainly composed of cyanobacteria were removed through pressurized water. We monitored the artist's work through analyses of images and colorimetric variations and such drawings showed a duration of 4 years in the natural conditions of recolonization. Here we show how the recolonization of treated and control areas, analyzed with the same methods, showed an increased duration, 3 years longer than under natural conditions in the case of Preventol R80® and Biotin R® plus Silo 111®. The tested solutions showed differential effectiveness and multiple possibilities of use to support the maintenance of the artwork if the artist wanted to preserve his artwork for a longer period.